Between the River and the City. Resilience VS Vulnerability in Settlement Systems of Fluvial Environment - Filippo Angelucci; Michele Di Sivo; Daniela Ladiana (Techne, 2014)
In the presence of increasingly frequent extreme weather phenomena, water management in complex settlement areas, such as those located in a fluvial environment, involves not only the reduction of that area’s fragility but, more importantly, the regeneration of the lost interactions between the physical, economic and social dimensions of the area. Research conducted along the Pescara river has taken up this challenge, reinterpreting the critical environmental situation of the case study areas as the chance to oversee a more ample “water project” which could tackle the vulnerability of the territory by identifying new means of resilience and responsiveness to adverse natural events and by carrying out proactive coexistence scenarios between cities, inhabitants, institutions and natural resources.